Interferon-gamma producing regulatory T cells as a diagnostic and therapeutic tool in organ transplantation - Daniel, Volker; Wang, Haihao; Sadeghi, Mahmoud; Opelz, Gerhard (International reviews of immunology, 2014)
There is increasing evidence that IFNg plays a major role in both induction of Tregs as well as immunosuppression mediated by IFNg-producing Tregs. The present review focuses on a small subset of iTregs that produces IFNg, comprises only 0.04% of all CD4+ T lymphocytes in the blood of healthy individuals, and increases strongly during an immune response. IFNg+ Tregs are induced by IFNg and IL12, making them sensors for inflammatory cytokines. They develop rapidly during inflammation and represent the first line of Tregs that suppress initial immune responses. The pool of IFNg+ Tregs consists of activated stable immunosuppressive thymus-derived nTregs as well as peripherally proliferating iTregs with in part only transient immunosuppressive function, which limits their diagnostic and therapeutic usefulness in organ transplantation. Apparently, a part of IFNg+ Tregs dies during the immune response, whereas others, after efficient immunosuppression with resolution of the immune response, differentiate toward Th1 lymphocytes. Goals of further research are the development of appropriate diagnostic tests for rapid and exact determinination of immunosuppressive IFNg+ iTregs, as well as the induction and propagation of stable immunosuppressive IFNg+ Tregs that establish and maintain good long-term graft function in transplant recipients.